Detection of SARS-CoV-2 RNA and Antibodies in Diverse Samples: Protocol to Validate the Sufficiency of Provider-Observed, Home-Collected Blood, Saliva, and Oropharyngeal Samples - Sullivan, Patrick Sean; Sailey, Charles; Guest, Jodie Lynn; Guarner, Jeannette; Kelley, Colleen; Siegler, Aaron Julius; Valentine-Graves, Mariah; Gravens, Laura; del Rio, Carlos; Sanchez, Travis Howard (JMIR Publications, 2020)
BackgroundThe response in the United States to the coronavirus disease (COVID-19) pandemic has been hampered by a lack of aggressive testing for the infection. Testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cornerstone of an effective public health response. However, efforts to test have been hampered by limited reagents, limitations in the availability of swabs used for the collection of nasopharyngeal swab (NPS) specimens, limitations in personal protective equipment (PPE) for health care providers collecting the NPS specimens, and limitations in viral transport media for transporting the specimens. Therefore, more flexible options for screening for SARS-CoV-2 RNA and serologic responses are critical to inform clinical and public health responses. ObjectiveWe aim to document the ability of patients to self-collect sufficient specimens for SARS-CoV-2 viral detection and serology. MethodsPatient self-collection of samples will be done with observation by a health care provider during a telemedicine session. Participants will be mailed a specimen collection kit, engage in a telehealth session with a provider through a HIPPA (Health Insurance Portability and Accountability Act of 1996)-compliant video meeting, and collect specimens while being observed by the provider. Providers will record whether they are confident in the suitability of the specimen for laboratory testing that would inform clinical decision making. We will objectively assess the sufficiency of biological material in the mailed-in specimens. ResultsThe protocol was approved by the Emory University Institutional Review Board (IRB) on March 30, 2020 (Protocol number 371). To date, we have enrolled 159 participants. ConclusionsDefining a conceptual framework for assessing the sufficiency of patient-collected samples for the detection of SARS-CoV-2 RNA and serologic responses to infection is critical for facilitating public health responses and providing PPE-sparing options to increase testing. Validation of alternative methods of specimen collection should include objective measures of the sufficiency of specimens for testing. A strong evidence base for diversifying testing modalities will improve tools to guide public health responses to the COVID-19 pandemic.